Sacral agenesis and neurogenic bladder: Long-term outcomes of bladder and kidney function. Issue 3 (June 2016) - Cho, P.S.; Bauer, S.B.; Pennison, M.; Rosoklija, I.; Bellows, A.L.; Logvinenko, T.; Khoshbin, S.; Borer, J.G.
Summary: Background: Sacral agenesis (SA) is a rare congenital condition that refers to the absence of part or all of two or more lower sacral vertebral bodies. It can be associated with neurogenic bladder dysfunction that does not necessarily correlate with the level of spinal or skeletal defect. Patients with SA should undergo urodynamic studies (UDS) to guide lower urinary tract (LUT) management. Objective: This review aimed to update the present institutional experience since 1981 of this rare patient population with detailed, long-term follow-up of bladder and kidney function. Study design: A single institution, retrospective, IRB-approved review was performed on patients born after January 1, 1981 with an isolated diagnosis of sacral agenesis without spina bifida, and followed with urologic involvement at Boston Children's Hospital. Records were reviewed for demographics, radiologic imaging, UDS including cystometrogram (CMG) and electromyography (EMG), surgery, and blood chemistries. Comparisons were made between groups of patients based on age at diagnosis, with specific focus on renal function and stability of neurogenic bladder lesion. Results: Forty-three patients were identified: 23 female and 20 male. Thirty-seven children (86%) had a known age of diagnosis. Nineteen were diagnosed before 2 months old, including five who were diagnosed prenatally, 11 were diagnosed between 2 and 18 months, and seven were diagnosed after 18 months. All 43 had UDS, with 24 (55.8%) studied at the time of diagnosis (Summary Table ). Twenty had serial full UDS, with 30% demonstrating neurourologic instability. None developed end-stage renal disease (ESRD) or required spinal cord detethering. Discussion: Many children with SA appeared to be diagnosed prenatally or early in life; SA was mostly identified during evaluation of associated anomalies. Though UDS aid in urologic management, testing was not routinely utilized at the time of diagnosis. Conclusions: This review of long-term follow-up in SA patients showed stable LUT and renal function, with minimal risk of progression to ESRD. Summary Table Group 1 Group 2 Group 3 Group 4 Adjusted P -value Age at diagnosis <2 months 2–18 months >18 months unknown n 19 11 7 6 Most recent method of bladder emptying Voiding 7 (36.8%) 3 (27.3%) 2 (28.6%) 1.00 CIC 13 (68.4%)* 8 (72.7%) 5 (71.4%) 1.00 No hydronephrosis on recent ultrasound 13 (68.4%) 5 (45.5%) 3 (42.8%) 0.90 Recent serum creatinine (ng/dl) Median 0.4 0.4 0.55 0.91 IQR 0.3–0.5 0.4–0.7 0.4–0.8 0.91 *One patient utilized both CIC and voiding to empty.